PENERAPAN METODE PEMBELAJARAN ROLE PLAY UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR KETRAMPILAN BERBICARA BAHASA INGGRIS - Lukman Hakim (LPPM UNISDA, 2020)
The aim of this research is to improve learning outcomes of speaking ability and response in English through “Role Play” in SMPM 27 Paciran Lamongan. The subject of the research is grade IX students of the first semester in the academic year of 2018/2019 consisting of 21 pupils. To collect the data, the researcher uses observation sheet and the result of speaking test. The research proses was conducted into two cycles, each cycle consisting of four phases : preparation, implementation, obeservation and reflection. The findings of the research show that Role Play method is effective to improve the students’ activities and the result of speaking test. From the result of the analysis showed that there is an increase of students’ activities in cycle 1 from 76% into 88% on second cycle. The result of speaking test in English increase from the completeness of learning from 57% in cycle 1 into 81% in cycle 2.